Market-driven indian bank merger announcements and stock returns - T., Senthil Kumar; Mohd Ridzuan, Darun; Aslam, Mohammad (Institute of Advanced Scientific Research, 2020)
The Government of India, Reserve Bank of India and bank managers, in general, favour bank consolidation for various reasons. They support consolidation to create a few large global banks, to achieve rapid growth and to gain from economies of scale and scope. However, international studies and Indian studies on bank mergers indicate that the evidence in favour of bank mergers is mixed, at best. Hence, this study was conceived to analyse the effect of market-driven Indian bank-to-bank mergers on stockholders during the post-reform period, 1999 – 2014. Event study analysis was performed using the „market model‟ with the BSE-500 stock index as the reference index. Each merger announcement was considered as an event and daily stock returns in a 30-day time window were computed before and after the event. Overall, if the abnormal returns had been positive it could be implied that merger announcements have a positive impact on the stock prices. However, the results indicate that stock returns of acquiring banks and acquired banks generally declined in the time period around merger announcement. In the case of acquiring banks, adverse reaction was observed in six out of nine mergers that were analysed. Among the nine acquired banks, five were listed and adverse reaction was noted in three cases. Overall, merger announcements appear to have had an undesirable effect on stock returns of acquiring and acquired banks. Hence, future merger decisions should be taken only if other alternatives are not available and such decisions must be driven by due diligence.